Some properties of weight functions in tauberian theorems - Olenko, A.; Klykavka, B. (Інститут математики НАН України, 2006)
The rate of convergence for weight functions series in Tauberian theorems is obtained. Numerical results demonstrate required rate of convergence.
Some asymptotic properties of hypergeometric functions are
obtained as auxiliary results.